2015
DOI: 10.1016/j.bej.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assessment of a graphene-based composite photocatalyst

Abstract: A novel composite photocatalyst prepared from graphene and commercial TiO2 (P25 from Evonik) was synthesized, exhibiting enhanced photocatalytic activity for methylene blue degradation, when com-pared with pristine P25. Additionally, the new catalyst showed 20% more NO conversion under UV light than P25. The band gap of the catalyst, obtained from diffuse reflectance, was 2.95 eV indicating an extended light absorption up to 420 nm. The novel photocatalyst was further tested for inactivating microorganisms sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The lower band gap of the composite can be explained by titanium dioxide doping by carbon from graphene, which can act as substitutional anion or an interstitial cation, substituting oxygen or titanium, respectively. The carbon doping of titanium dioxide leads then to a narrowing in band gap and a consequent redshift in the absorption spectrum of the composite [25,34]. The P25/graphene photocatalyst band gap is in good agreement with values reported for equivalent materials [15,16,35].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The lower band gap of the composite can be explained by titanium dioxide doping by carbon from graphene, which can act as substitutional anion or an interstitial cation, substituting oxygen or titanium, respectively. The carbon doping of titanium dioxide leads then to a narrowing in band gap and a consequent redshift in the absorption spectrum of the composite [25,34]. The P25/graphene photocatalyst band gap is in good agreement with values reported for equivalent materials [15,16,35].…”
Section: Resultssupporting
confidence: 83%
“…In a previous work [25], the crystallographic characterization of P25 and P25/graphene composite was performed by X-ray diffraction (XRD). These photocatalysts showed similar XDR patterns.…”
Section: Figures 3 and 4 Present Sem Images Of Top View (A) And Crossmentioning
confidence: 99%
“…These observations are in line with other works published elsewhere . In fact, the adsorption capacity of graphene sheets is about fourfold higher than pure P25 and twofold higher than P25‐GR . Nguyen‐Phan et al reported the photodegradation of methylene blue by TiO 2 ‐GR composite photocatalysts and also found enhanced performance of this composite when compared with pure TiO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 91%
“…Since the work of Willians, Seger and Kamar there is an increasing interest in the use of graphene‐based composite semiconductors for photocatalytic processes due to their outstanding properties. According to previous findings, the enhanced activity of TiO 2 ‐GR may be attributed to the decrease in e − /h + recombination, since graphene has the ability to accept the electrons photogenerated by P25, as well as the increased adsorption of methylene blue on the graphene sheets. These observations are in line with other works published elsewhere .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation